2015
DOI: 10.1371/journal.pone.0131650
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Obesity Specific MicroRNA Expression in Adipose Tissue from Lean and Obese Pigs

Abstract: Obesity is a complex condition that increases the risk of life threatening diseases such as cardiovascular disease and diabetes. Studying the gene regulation of obesity is important for understanding the molecular mechanisms behind the obesity derived diseases and may lead to better intervention and treatment plans. MicroRNAs (miRNAs) are short non-coding RNAs regulating target mRNA by binding to their 3’UTR. They are involved in numerous biological processes and diseases, including obesity. In this study we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 76 publications
2
41
3
Order By: Relevance
“…Similar studies for miRNA expression have also been reported in male and female samples474849, and relationships of miRNA expression and sex differences have attracted the attention of researchers. Herein, for the specific disease, the two groups with gender-difference, LUAD-male and LUAD-female groups, showed inconsistent miRNA and mRNA expression patterns and fewer common RNAs (Figs 1, 2, 3 and S1).…”
Section: Discussionsupporting
confidence: 67%
“…Similar studies for miRNA expression have also been reported in male and female samples474849, and relationships of miRNA expression and sex differences have attracted the attention of researchers. Herein, for the specific disease, the two groups with gender-difference, LUAD-male and LUAD-female groups, showed inconsistent miRNA and mRNA expression patterns and fewer common RNAs (Figs 1, 2, 3 and S1).…”
Section: Discussionsupporting
confidence: 67%
“…This research emphasizes the value of a porcine model for human obesity. Moreover, in our previous research we have shown that miRNAs are differentially expressed in lean versus obese pigs from the same pig population, confirming their relevance in obesity studies [10]. One challenge with working with the pig as a model for miRNA studies is the issue of miRNA target finding.…”
Section: Introductionmentioning
confidence: 58%
“…In total, 40 protein-coding genes and 18 miRNAs were significantly differentially expressed with fold changes larger than 1.5 suggesting important differences in obesity-relevant gene expression between lean and obese Göttingen minipigs. We expected to encounter a large number of differentially expressed protein-coding genes and miRNAs in this study, since the genes included were individually selected, based on results from previous obesity studies in pigs and other organisms as well as unpublished information obtained from conferences [9,10,1820]. Previous studies using the same animals have shown significant differential expression of several other inflammation (mainly genes involved in innate immunity) and obesity relevant genes in multiple tissues as well as a slight enlargement of the adipocytes within the obese minipigs [20,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations